An optimum design of implosion with external magnetic field for electron beam guiding in fast ignition. (May 2016) - Nagatomo, H; Johzaki, T; Asahina, T; Matsuo, K; Sunahara, A; Sakagami, H; Sano, T; Mima, K; Morace, A; Zhang, Z; Fujioka, S; Shigemori, K; et al.
Abstract: Compression of solid spherical target under the strong external magnetic field is studied using two dimensional radiative magneto-hydrodynamic (MHD) simulation code for fast ignition. The simulation results show that a compression of a solid sphere target is stable, and it is possible to achieve a high areal density core plasma. Assuming the GXII scale laser, it will be ρR =60-80mg/cm 2 . Due to the magnetic diffusion in the solid target, the magnetic mirror ratio is less than 4, which does not reflect most of the hot electrons for heating core. These properties are preferable for fast ignition scheme.